Effects of hispolon on glioblastoma cell growth. Issue 9 (15th June 2017) - Arcella, Antonietta; Oliva, Maria Antonietta; Sanchez, Massimo; Staffieri, Sabrina; Esposito, Vincenzo; Giangaspero, Felice; Cantore, Giampaolo
Abstract: Hispolon is a polyphenolic compound isolated from Phellinus linteus which exhibits antitumor activity. Here, we explored the effects of hispolon on human glioblastoma cells U87MG. Cell viability was examined by MTT assay. Growth was investigated by incubating cells with various concentrations of hispolon (25 and 50 µM) for 24, 48 or 72 h and daily cell count. Cell cycle and apoptosis assay were assessed by flow cytometry. Hispolon decreased cell viability in a dose‐ and time‐dependent manner. The cell cycle distribution showed that hispolon enhanced the accumulation of the cells in G2/M phase. Hispolon decreased the expression of G1–S transition‐related protein cyclin D4 but increased the expression of CDK inhibitor p21. Additionally, hispolon enhanced the expression of p53. Moreover, hispolon treatment was effective on U87MG cells in inhibiting cell viability and inducing cell apoptosis. Our results indicate that hispolon inhibits the cell viability, induces G2/M cell cycle arrest and apoptosis in glioblastoma U87MG cells, and p53 should play a role in hispolon‐mediated antitumor activity.